Bionic Functional Structures by Femtosecond Laser Micro/nanofabrication Technologies - Li, Guoqiang; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2018)
This thesis combines advanced femtosecond laser micro/nanofabrication technologies and frontier bionic design principles to prepare diverse biomimetic micro/nanostructures to realize their functions. By studying the formation mechanism of the micro/nanostructures, the author identifies various artificial structural colors, three-dimensional micro/nanocage arrays, and fish-scale inspired microcone arrays in different processing environments. Multiple functions such as enhanced antireflection, hydrophobicity, and underwater superoleophobicity are achieved by precisely adjusting laser-machining parameters. This novel design and method have extensive potential applications in the context of new colorizing technologies, microfluidics, microsensors, and biomedicine.
Introduction -- Key technological of bionic structure surfaces induced by femtosecond laser -- Bionic structure induced by femtosecond laser -- PDMS surface wetting based on metal template by femtosecond laser -- Three-dimensional porous metal micro/nano cage structure by femtosecond laser with ethanol assisted -- Superhydrophilic/ underwater superoleophobic microcone arrays by sucrose solution assisted femtosecond laser -- Conclusion and Outlook.
Keywords: Nanotechnology; Nanochemistry; Atoms; Molecules; Surfaces (Technology).; Thin films; Lasers; Nanotechnology; Nanochemistry; Atoms and molecules in external fields; Surfaces, Interfaces and Thin Film; Laser